PEMANFAATAN LIMBAH GROUND GRANULATE BLAST FURNACE SLAG (GGBFS) SEBAGAI BAHAN GEOPOLIMER UNTUK STABILISASI TANAH DASAR (SUBGRADE) - Indera Kusuma, Rama; Cahyani, Fadhila Putri; Mina, Enden; Fathonah, Woelandari (Direktorat Bina Teknik Jalan dan Jembatan, 2024)
Ground Granulate Blast Furnace Slag (GGBFS) is a by-product or non-metallic waste from the iron and steel production process. GGBFS is currently widely applied as an additive to mortar mixtures because it has pozzolanic properties. It can also be used as a material for stabilizing subgrade soil that is not included in the technical requirements for road pavement. GGBFS is a geopolymer material with NaOH and Na2SiO3 as an alkali activator to produce a solid polymer bond like cement. The concentration of 10 M NaOH used is with a solution ratio of 2.0 (Na2SiO3 to NaOH), variations in GGBFS content of 0% and 20%, and variations in S/L content (GGBFS to activator) of 1/2 and 1/2.5; which is mixed with the original soil to make a sample of an Unconfined Compression Test (UCT), with the curing of the UCT test specimens carried out for 0, 7, 14, and 28 days. From the test results, the original soil sample is of the OH soil type. The results of UCT testing of original soil samples without stabilization with a curing time of 28 days were 1.59 kg/cm2, while the stabilized soil sample (80% soil, 20% GGBFS, alkali activator S/L (1/2.5)) was 29.386 kg/cm2. The results of UCT testing showed a significant increase in soil strength values ​​, so geopolymers with GGBFS and (NaOH; Na2SiO3) materials can be used as soil stabilization materials like Portland cement.